Distribusi Tenaga Kesehatan di Kalimantan Barat Menggunakan Metode Ward: Distribution of Health Workers in West Kalimantan Using the Ward Method - Endah Saraswi; Hendra Perdana; Anis Fakhrunnisa (Badan Pusat Statistik Provinsi Kalimantan Barat, 2024)
West Kalimantan's population has increased significantly in a fairly short period of time, with a growth of 11% in the last five years. The challenge in ensuring the welfare of the community, especially in the aspect of health. This study aims to fill the research gap by clustering regions using the Ward’s method to see if the distribution of health workers in West Kalimantan reflects and has an impact on the level of Life Expectancy (LE). The data utilized includes the number of health workers consisting of doctors, nurses, midwives, and nutritionists. The data was processed by calculating the ratio of population to the number of health workers in each region to provide a comprehensive picture of the distribution and availability of health workers in West Kalimantan. Cluster analysis method was used in this study. The results of the analysis show that the proportion of health workers and the LE level in West Kalimantan have a positive correlation. Based on Ward's dendrogram method, 14 districts/cities in West Kalimantan were divided into four clusters. Over a period of five years, there were seven areas that experienced cluster shifts, indicating the dynamics of health worker distribution. The government is advised to continue to pay attention to the distribution and availability of health workers in all regions in order to improve community welfare.